INDONESIAN ANTI-TRUST RELAXATION: URGENCY FOR IMPLEMENTATION PROVISION AND ITS CORRELATION WITH GOTONG ROYONG PRINCIPLE - Tresnawati Tresnawati (Faculty of Law Universitas Padjadjaran, 2022)
ABSTRACT During the Covid-19 pandemic, numerous jurisdictions have used Anti-Trust Relaxation, also known as Anti-Trust Immunity (ATI) in the United States, recognized as block exemption, authorization, or dispensation in other jurisdictions. Essentially, this ATI states that collaboration between business actors does not always imply an infringement in competition. There are times when cartels and teamwork can be beneficial to the environment. Many businesses have suffered enormous losses because of the Covid-19 outbreak, and they require assistance and support to survive in this unique scenario. Most likely, survival is only possible when business competitors embrace 'gotong royong' or collaboration. Anti-trust immunity, which allows collaboration-usually defined as cartel in normal situation-will be assessed and authorized accordingly by Business Competition Supervisory Commission (KPPU). Another possibility is to include this ATI in the new bill, which would be even more authoritative. On November 2020, KPPU Regulation No. 3 of 2020 on Competition Relaxation was enacted. However, detailed implementation provision will be required in implementation of the Regulation. Keywords: anti-trust immunity; authorization; block exemption; cartel relaxation; dispensation.